Making the most of public policy in health libraries and information services: Example of the Health and Care Bill 2022. (17th May 2022) - Carlyle, Ruth
Abstract: Public policy changes, such as new legislation, can seem distant from health knowledge and libraries services. The changes can provide, however, opportunities for health libraries and information services across sectors to demonstrate their value, supporting their ongoing funding and integration. The Health and Care Bill 2022 is an example of a public policy change that has specific implications in England, but also demonstrates the elements to look out for in new legislation as opportunities for health libraries and information services.